Linking the morphology of a high hard segment content polyurethane to its thermal behaviour and mechanical properties. (16th December 2015) - Swolfs, Y.; Bertels, E.; Verpoest, I.; Goderis, B.
Abstract: Understanding and controlling the morphology of thermoplastic polyurethane (TPU) is crucial, as it is closely linked with its thermal and mechanical properties. The morphology of a TPU with a high hard segment content was investigated. When hard segment crystallisation was avoided by fast cooling, a crystallisation-induced phase separation occurred upon reheating. At higher temperatures, a second polymorph was additionally created. Cooling slowly from the melt directly induced the formation of both polymorphic forms. The complex thermal behaviour could hence be explained by the (cold) crystallisation and melting of two polymorphs. The disordered two-phase nanomorphology, revealed by AFM at room temperature after cooling slowly, was validated for both fast and slowly cooled samples at higher temperatures by fitting model SAXS patterns to time resolved synchrotron SAXS data. Annealing fast cooled samples at high temperature induced some ordered, lamellar stacks in addition. Finally, the morphology was linked to the evolution of storage modulus with increasing temperature. Graphical abstract: Highlights: The morphology of a high hard segment content TPU was investigated. The morphology was disordered or lamellarly ordered depending on thermal history. Fitting the SAXS patterns revealed morphology changes as a function of temperature. Changes in storage modulus were linked to changes in the morphology.